A genetic variant controls interferon-β gene expression in human myeloid cells by preventing C/EBP-β binding on a conserved enhancer. - Anaïs Assouvie (PLoS Genetics, 2020)
Interferon β (IFN-β) is a cytokine that induces a global antiviral proteome, and regulates the adaptive immune response to infections and tumors. Its effects strongly depend on its level and timing of expression. Therefore, the transcription of its coding gene IFNB1 is strictly controlled. We have previously shown that in mice, the TRIM33 protein restrains Ifnb1 transcription in activated myeloid cells through an upstream inhibitory sequence called ICE. Here, we show that the deregulation of Ifnb1 expression observed in murine Trim33-/- macrophages correlates with abnormal looping of both ICE and the Ifnb1 gene to a 100 kb downstream region overlapping the Ptplad2/Hacd4 gene. This region is a predicted myeloid super-enhancer in which we could characterize 3 myeloid-specific active enhancers, one of which (E5) increases the response of the Ifnb1 promoter to activation. In humans, the orthologous region contains several single nucleotide polymorphisms (SNPs) known to be associated with decreased expression of IFNB1 in activated monocytes, and loops to the IFNB1 gene. The strongest association is found for the rs12553564 SNP, located in the E5 orthologous region. The minor allele of rs12553564 disrupts a conserved C/EBP-β binding motif, prevents binding of C/EBP-β, and abolishes the activation-induced enhancer activity of E5. Altogether, these results establish a link between a genetic variant preventing binding of a transcription factor and a higher order phenotype, and suggest that the frequent minor allele (around 30% worldwide) might be associated with phenotypes regulated by IFN-β expression in myeloid cells.